2005
DOI: 10.1017/s0020859005002075
|View full text |Cite
|
Sign up to set email alerts
|

“We Have No Proletariat”: Social Stratification and Occupational Homogamy in Industrial Switzerland, Winterthur 1909/10–1928

Abstract: The aim of this study is to examine, by analysing marital origin-related homogamy and mobility, the fluidity of a system of social stratification marked by a heterogeneous working class and likely to lead to increasing social-group solidarity during the phase of a more active labour movement in the early twentieth century. Data from Winterthur, a Swiss town characterized by the expansion of an important engineering industry, reveal that occupational homogamy was most pronounced at the top, among higher manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Since the DOT was constructed for modern-day occupations these grades were adjusted with help of expert historians which was only necessary in a few cases and finally led to 12 distinct social classes. In our empirical analysis we rely on the previous literature and use a compressed 7-class version of HISCLASS (see Abramitzky et al (2011) and Schumacher and Lorenzetti (2005) and references therein). This simplifies the interpretation of regression coefficients, attenuates possible coding errors and increases sample size within classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the DOT was constructed for modern-day occupations these grades were adjusted with help of expert historians which was only necessary in a few cases and finally led to 12 distinct social classes. In our empirical analysis we rely on the previous literature and use a compressed 7-class version of HISCLASS (see Abramitzky et al (2011) and Schumacher and Lorenzetti (2005) and references therein). This simplifies the interpretation of regression coefficients, attenuates possible coding errors and increases sample size within classes.…”
Section: Discussionmentioning
confidence: 99%
“…33 This allowed us to use equivalent HISCLASS codes of military ranks as a benchmark for police, postal, railway, educational and other governmental HISCO codes and adjust the previously assigned HISCLASS codes if there were large discrepancies. Schumacher and Lorenzetti (2005) and Van Leeuwen and Maas (2011) Notes: Other economic sector refers to the industrial or service sector. Classes 1 and 3 of the original HISCLASS system contain only 3 occupations which are in the primary sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schumacher and Lorenzetti (2005) document occupational homogamy between 1909 and 1928 in Winterthur and revealed particularly high levels among managers and unskilled factory workers. Studies that use more recent survey data and three educational levels report 68% of homogamous couples in 1994 (Diekmann and Schmidheiny 2001) and 63% in 2008Bühlmann and Schmid Botkine (2012.…”
Section: Assortative Mating and Educationmentioning
confidence: 99%
“…Also, some studies have indicated that the stratification failed to expand the social borders in marriage practices (e.g. Schumacher & Lorenzetti, 2005).…”
Section: Differences In Demographical and Industrial Characteristicsmentioning
confidence: 99%